Design and Evaluation of a Spoke-Based Double-Lumen Pediatric Gastrostomy Tube - Mihika Aedla; Charlotte J. Cheng; Anson Y. Zhou; Siya Zhang; Jocelyn Hsu; Katherine Hu; Jason C. Qian; Kevin Van de Sompel; Anthony Ho; Karun V. Sharma; Elizabeth A. Logsdon (MDPI AG, 2024)
Gastrostomy tubes (G-tubes) are the gold standard for feeding assistance for children with feeding dysfunction. Current G-tubes pose complications that interrupt the delivery of feed, including tube displacement and difficulty of at-home use. This study details an alternative, spoke-based, double-lumen G-tube design and preliminary validation of its function and usability. Pull force testing was performed on spoke G-tube models across three sizes and two classifications (hard/soft). Preliminary models were evaluated against market standards. Though the pull force of the spoke model was found to be lower than that of both market standards, hard modifications to the spoke model improved retentive force. Ease of use was tested amongst users unfamiliar with G-tube placement. The spoke design required 12.3 ± 4.7 s to deploy, less than half the time required for market standards. However, balloon G-tubes were still perceived to be easiest to use by 70% of participants, with indications that a spoke design may be easier to use if sized similarly to current G-tubes, with auxiliary improvements to factors such as grip. While there is a need for improvements in the material properties and manufacturing of the proposed design, this study provides early validation of the potential to address complications of existing G-tubes.